ACE inhibitory peptide KYIPIQ derived from yak milk casein induces nitric oxide production in HUVECs and diffuses via a transcellular mechanism in Caco-2 monolayers. (December 2020) - Lin, Kai; Ma, Zhao; Ramachandran, Mythili; De Souza, Cristabelle; Han, Xue; Zhang, Lan-wei
Graphical abstract: Abstract: The purpose of this study was to explore the effects of KYIPIQ, an angiotensin I-converting enzyme (ACE) inhibitory peptide found in yak milk casein, on the production of nitric oxide (NO) in human vascular endothelial cells (HUVECs). Additionally, we also sought to study the transport pathway of this peptide across monolayers of the human epithelial colorectal adenocarcinoma cell line (Caco-2). Treatment with peptide KYIPIQ increased NO synthesis and expression of phosphorylated endothelial nitric oxide synthase (eNOS) in HUVECs. Our results demonstrate that KYIPIQ-induced eNOS phosphorylation is dependent on the protein kinase B (Akt) activation pathway. Furthermore, our data indicate that the peptide KYIPIQ can be transported across the Caco-2 cell monolayer and that paracellular transport is the main transcellular mechanism. Thus, our studies suggest that KYIPIQ can be potentially used as a therapeutic agent for the treatment of hypertension.